Challenging the "integration imperative": A customer perspective on omnichannel journeys - Gasparin Isadora; Panina Ekaterina; Becker Larissa; Yrjölä Mika; Jaakkola Elina; Pizzutti Cristiane (Elsevier, 2022)
Omnichannel literature largely assumes that retailers should integrate touchpoints across channels to promote seamless experiences. This paper challenges this assumption by exploring how perceived journey integration affects customer experience in omnichannel retailing. A qualitative study reveals that two dimensions of journey integration—consistency and connectivity—interact to form four patterns of omnichannel journeys, each prompting distinct experiences. When looking at this phenomenon through the customer’s perspective, we find that there are cases in which low consistency or connectivity can trigger positive experiences, contradicting extant literature. We then formulate research propositions that challenge the “integration imperative” in the omnichannel literature and provide managerial implications for retail firms that want to improve their customers’ experiences.